Microwave-Assisted Solvent Free Synthesis of Spiro-Indole Derivative - Mishra, A D (Journal of Nepal Chemical Society, 2009)
A solid supported synthetic procedure has been developed for the synthesis of novel spiro indole derivatives using solid support as energy transfer medium under microwave irradiation (MWI). The results were compared with those obtained by the classical as well as solution phase method in MWI. This solvent-free technique coupled with the high yields and short reaction time makes this procedure eco-friendly for synthesis.  Keywords: Spiro indoles; Microwave irradiation; 1HNMR; IRDOI: 10.3126/jncs.v24i0.2391 Journal of Nepal Chemical Society Vol. 24, 2009 Page: 49-52